What has Changed After the Great Recession on the European Cyclical Patterns? - Rodriguez-Santiago, Ana (Springer, 2019)
This article analyses the business cycle dynamics in the European Union (EU28) during recent decades. Following Camacho et al. (J Econ Dyn Control 30:1687–1706, 2006), we extend the analysis of European cycles to a broader range of countries, including new entrants. In addition, we update their sample by including the Great Recession data with the aim of exploring whether the financial crisis led to changes in cyclical features across these countries. Our results indicate that the Great Recession has undermined European cyclical linkages. Notably, we succeeded in detecting that the European economies do not follow more closed dynamics, despite the fact that the countries are showing more similar cyclical characteristics.
Keywords: Ciclos económicos; Crisis financieras - Europa; Business cycle characteristics; Cyclical synchronization; European Union enlargement